Partial Anomalous Pulmonary Venous Connections: Surgical Management. (January 2013) - Fragata, José; Magalhães, Manuel; Baquero, Luis; Trigo, Conceição; Pinto, Fátima; Fragata, Isabel
Partial anomalous pulmonary venous connections (PAPVCs) are a heterogeneous group of congenital heart lesions in which at least one pulmonary vein will drain into the systemic venous system. The consequences are a variable left-to-right hemodynamic shunt and more rarely pulmonary artery hypertension. Often, PAPVC occurs in association with other congenital cardiac malformations. Surgical correction is most often advisable and is generally straightforward and simple to achieve. Historically, some repairs have included incision across the junction of the superior vena cava with the right atrium, which can lead to late arrhythmias. The Warden technique avoids incision across the atriocaval junction. Neonates and infants with Scimitar syndrome represent the most challenging subset of patients with PAPVC.